2007
DOI: 10.1007/s12098-007-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic pharyngeal pseudodiverticulum mimicking esophageal atresia

Abstract: Obstruction of passage of a catheter through esophagus in a newborn is mostly diagnosed as esophageal atresia (EA) with or without tracheo esophageal fistula (TEF). Rarely a traumatic instrumentation may produce pharyngeal or upper esophageal perforation and attempt at passage of a catheter may produce a false passage submucosally called pseudodiverticulum. Here it is present the case of a extremely premature (28 wk) and low birth weight (950 gms) newborn with traumatic laceration and pharyngeal pseudodivertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Inability to insert a nasogastric tube and barium imaging results can easily be misinterpreted as symptoms of esophageal atresia [10,11]. The patient studied in our report had none of these signs with onset of symptoms at the age of 5 months.…”
Section: Discussionmentioning
confidence: 80%
“…Inability to insert a nasogastric tube and barium imaging results can easily be misinterpreted as symptoms of esophageal atresia [10,11]. The patient studied in our report had none of these signs with onset of symptoms at the age of 5 months.…”
Section: Discussionmentioning
confidence: 80%
“…Few cases are reported that allow no valid conclusions as to their etiology [25]. Pulsion diverticulum is rare in children, and the reported cases were 6-month-to 10-year-old children.…”
Section: Esophageal Diverticulummentioning
confidence: 99%